Promoting and producing evil - Billias, Nancy (At the interface/probing the boundaries, 2010)
The essays in this volume provide rich fodder for reflection on topics that are of urgent interest to all thinking people. Each one suggests new ways to contemplate our own role(s) in the production and promotion of evil. The authors encourage the reader to be challenged, outraged, and disturbed by what you read here. The eighth gathering of Global Perspectives on Evil and Human Wickedness, which took place in Salzburg in March 2007, provided a look at evil past, present, and future, from a broad spectrum of disciplinary perspectives. Papers were presented on the Holocaust, genocide, violence.